2020
DOI: 10.2169/internalmedicine.3889-19
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis in a Patient with Rheumatoid Arthritis on Pembrolizumab for Lung Adenocarcinoma

Abstract: Immune checkpoint inhibitors have changed the landscape of classic cancer treatment. However, their use is associated with the emergence of new adverse events. An elderly man with rheumatoid arthritis was started on pembrolizumab for newly diagnosed advanced lung cancer. He subsequently developed hemophagocytic lymphohistiocytosis (HLH), which is potentially fatal but has not been properly established as an immune checkpoint inhibition-induced event. We herein report the case of a patient with pembrolizumab-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…One literature review includes 16 reports involving a total of 20 patients who were diagnosed with HLH secondary to a solid tumor (Table 2). Among the patients, 8 received immune checkpoint inhibitors (16)(17)(18)(20)(21)(22)(23)(24), 8 underwent chemotherapy (11)(12)(13)(14), and 4 were only diagnosed with a solid tumor (9,10,15,19). Thus, the application of immunotherapy as well as some HLH patients who are misdiagnosed as neoplastic fever may increase the incidence of HLH, which requires more attention.…”
Section: Epidemiologymentioning
confidence: 99%
“…One literature review includes 16 reports involving a total of 20 patients who were diagnosed with HLH secondary to a solid tumor (Table 2). Among the patients, 8 received immune checkpoint inhibitors (16)(17)(18)(20)(21)(22)(23)(24), 8 underwent chemotherapy (11)(12)(13)(14), and 4 were only diagnosed with a solid tumor (9,10,15,19). Thus, the application of immunotherapy as well as some HLH patients who are misdiagnosed as neoplastic fever may increase the incidence of HLH, which requires more attention.…”
Section: Epidemiologymentioning
confidence: 99%
“…The fever and splenomegaly may be signs of enhanced immune activation. Previous research has shown that diseases that present prior to the diagnosis of HLH, such as thyroiditis, appendicitis, edema, and flareup of preexisting ADs, may be the expression of immune overactivation (19,(22)(23)(24). Moreover, markedly elevated interleukin (IL)-6 was detected in both patients, which could be a possible treatment target for HLH.…”
Section: Discussionmentioning
confidence: 97%
“…We reviewed 11 cases of ICIinduced HLH, including our cases (Table 3). [4][5][6][7][8][9][10][11] The median interval from the last dose to HLH diagnosis was 24 days; therefore, the two patients discussed in our report were diagnosed in the late phase. Based on the time interval, cases in which HLH was diagnosed after a long interval showed a lower HScore than those diagnosed after a short interval (Figure 2).…”
Section: Discussionmentioning
confidence: 99%